2022
DOI: 10.26773/mjssm.220303
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Age Effect on Athletes of the Santa Catarina Basketball Federation

Abstract: This study analyses the relative age effect (RAE) in basketball athletes, considering the categories (U13, U15, U17, and U19), sex, number of games and average points. The participants were 1,455 Brazilian athletes aged between 9 and 19 who participated in the Santa Catarina State Basketball Championship in the 2018 season. To test the RAE, the Chi-square test (χ2) was performed to compare the observed distribution and expected birth quartiles. To verify the differences between the birth quartiles concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This study's findings support the notion that geographical and regional factors may also influence RAE in basketball at the Youth Olympic Games level. Research by Maciel et al 23 revealed a similar RAE trend in the Santa Catarina State Basketball Championship, particularly affecting male players in the U13 category. The study 24 suggests that the training methodologies used in youth sports could further exacerbate RAE.…”
Section: Discussionmentioning
confidence: 67%
“…This study's findings support the notion that geographical and regional factors may also influence RAE in basketball at the Youth Olympic Games level. Research by Maciel et al 23 revealed a similar RAE trend in the Santa Catarina State Basketball Championship, particularly affecting male players in the U13 category. The study 24 suggests that the training methodologies used in youth sports could further exacerbate RAE.…”
Section: Discussionmentioning
confidence: 67%
“…Although this strategy aims at a fairer competitive environment, it ends up benefiting athletes who were born closer to the cut-off date (Leite, Arede, Shang, Calleja-González, & Lorenzo, 2021;Lidor, Maayan, & Arnon, 2021). This systematic overrepresentation of relatively older athletes in sports is known as the relative age effect (RAE) and has been reported especially among males in many competitive sports (Cobley, Baker, Wattie, & McKenna, 2009), both among youth (Castro, et al, 2023;Figueiredo, Seabra, Brito, Galvão, & Brito, 2021;Maciel, et al, 2022) and senior athletes (Castro, et al, 2022c;Figueiredo, et al, 2022;Lago-Fuentes, Rey, Padrón-Cabo, Prieto-Troncoso, & Garcia-Núñez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though RAE is a widespread phenomenon in different individual 20,21 and invasion team sports [22][23][24][25][26][27] , investigations in water sports focus on swimming [28][29][30] , being scarce in water polo [31][32][33] . In addition to that, the results from studies that investigated RAE in water polo are inconsistent.…”
Section: Introductionmentioning
confidence: 99%